Passing to India: a critique of American football’s expansion - Polson, Erika; Whiteside, Erin (Media, culture & society)
Although India has long held a passion for cricket, an organization called the Elite Football League of India (EFLI) is looking to disrupt that sporting nerve center, and introduce the foreign sport of American football to the country’s growing middle class. While it is too soon to assess how Indian audiences will respond to, negotiate and perhaps create new cultural practices around American football, we focus this article on an analysis of efforts made by promoters of the new league to create a cultural context in which this very foreign game might make sense. Drawing from press releases, promotional videos and news coverage, we demonstrate how language of social, economic and individual (male) development is deployed to create American football as a platform for delivering global brands to a vast Indian market. In deconstructing these efforts, we critically explicate how creative practices are implemented to produce an atmosphere within which globalization may occur.